PENGARUH SENAM SEHAT GEMBIRA TERHADAP KECERDASAN LOGIKA MATEMATIKA ANAK USIA 4-6 TAHUN PADA TAMAN KANAK-KANAK (TK) DI KECAMATAN CIRACAP KABUPATEN SUKABUMI TAHUN 2022 - Supardi, Astri Stania; Elnawati, Elnawati; Munajat, Asep (Universitas Muhammadiyah Ponorogo, 2025)
The purpose of this study is to examine the development of mathematical logic in children aged 4–6 years at kindergartens in Ciracap District, the implementation of joyful healthy gymnastics learning activities, and the significant influence of joyful healthy gymnastics on the mathematical logic intelligence of children aged 4–6 years at kindergartens in Ciracap District, Sukabumi Regency, in 2022. The research employed a quantitative method with a survey design to determine the influence of joyful healthy gymnastics on the mathematical logic intelligence of children aged 4–6 years, involving a sample of 54 respondents.The findings indicate that the development of children's mathematical logic is evidenced by a correlation coefficient of 0.534 with a 5% significance level. Thus, it can be concluded that there is a significant influence between joyful healthy gymnastics and the mathematical logic intelligence of children aged 4–6 years at kindergartens in Ciracap District, Sukabumi Regency, in 2022.